1996
DOI: 10.1172/jci118903
|View full text |Cite
|
Sign up to set email alerts
|

Insulin sensitivity index, acute insulin response, and glucose effectiveness in a population-based sample of 380 young healthy Caucasians. Analysis of the impact of gender, body fat, physical fitness, and life-style factors.

Abstract: Background. Insulin sensitivity and insulin secretion are traits that are both genetically and environmentally determined.Aim. The aim of this study was to describe the distribution of the insulin sensitivity index (Si), the acute insulin response, and glucose effectiveness (Sg) in young healthy Caucasians and to estimate the relative impact of anthropometric and environmental determinants on these variables.Methods. The material included 380 unrelated Caucasian subjects (18-32 yr) with measurement of Si, Sg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
202
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(226 citation statements)
references
References 67 publications
19
202
0
5
Order By: Relevance
“…Gylvin et al: [21]. s-C-peptide, serum C-peptide; p-glucose, plasma glucose; s-insulin, serum insulin [22] In conclusion, a mutation scanning of the human SOCS3 gene identified no variations associated with Type 1 diabetes mellitus. Homozygosity for a C −920→A promoter polymorphism with a minor allele frequency of 8% was shown to be associated with increased whole-body insulin sensitivity in a population of young healthy unrelated individuals.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Gylvin et al: [21]. s-C-peptide, serum C-peptide; p-glucose, plasma glucose; s-insulin, serum insulin [22] In conclusion, a mutation scanning of the human SOCS3 gene identified no variations associated with Type 1 diabetes mellitus. Homozygosity for a C −920→A promoter polymorphism with a minor allele frequency of 8% was shown to be associated with increased whole-body insulin sensitivity in a population of young healthy unrelated individuals.…”
mentioning
confidence: 78%
“…A random population-based sample of young, healthy, unrelated Danish subjects (n=370) from Copenhagen. Aged 18 to 32 years, these subjects underwent an IVGTT in combination with an intravenous tolbutamide injection [22].…”
Section: Introductionmentioning
confidence: 99%
“…15 Takemura et al 8 found that higher levels of fitness at baseline were protective against the development of IGT over a 20-year period. The protective effect of fitness was evident even after adjusting for baseline and follow-up BMI.…”
Section: Fitness and Glucose Tolerancementioning
confidence: 99%
“…The first consisted of 4444 middleaged NGT subjects, 490 subjects with IFG and 678 subjects with IGT, all of whom were from the Inter99 study and were examined by a standard 75-g OGTT with measurements of circulating levels of glucose, insulin and C-peptide at 0, 30 and 120 min. The second was a population-based sample of 358 young healthy subjects, who underwent a tolbutamide-modified IVGTT for measurements of the acute serum insulin and C-peptide responses as described previously [17]. Data on birth length and birthweight of the latter group were obtained from the midwife records stored in the Danish Provincial Archives for Zealand, Lolland-Falster and Bornholm.…”
Section: Subjectsmentioning
confidence: 99%
“…Acute serum insulin and serum C-peptide responses during a tolbutamide-modified IVGTT were calculated as the incremental area under the insulin/C-peptide curve for 0 to 8 min [17,18]. The insulin sensitivity index (S i ) was measured using Bergman's minimal model on data obtained during the IVGTT.…”
Section: Genotyping Of the Ins-vntr Class I And Class Iii Allelesmentioning
confidence: 99%